FUZZY APPROACHES TO SUPPLIER SELECTION PROBLEM - Ozkok, Beyza Ahlatcioglu; Kocken, Hale Gonce (AMER INST PHYSICS, 2013)
Supplier selection problem is a multi-criteria decision making problem which includes both qualitative and quantitative factors. In the selection process many criteria may conflict with each other, therefore decision-making process becomes complicated. In this study, we handled the supplier selection problem under uncertainty. In this context; we used minimum criterion, arithmetic mean criterion, regret criterion, optimistic criterion, geometric mean and harmonic mean. The membership functions created with the help of the characteristics of used criteria, and we tried to provide consistent supplier selection decisions by using these memberships for evaluating alternative suppliers. During the analysis, no need to use expert opinion is a strong aspect of the methodology used in the decision-making.
Keywords: Supplier selection problem; Fuzzy decision making; Multi-criteria decision making; VENDOR SELECTION; MULTIPLE CRITERIA; DECISION-MAKING; TOPSIS; CHAIN; MODEL; Mathematics; Physics